Artificial kidney - review article (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The important factors for the treatment of both acute and chronic renal failure are the proper regulation of diet and maintenance of water and electrolyte balance. The presence of anuria or oliguria requires the administration of large quantities of fluid attempts to initiate diuresis, resulting in an overload of salt and water and the appearance of symptoms leads to renal failure. Where dietary treatment, including rigid control of water and electrolytes, has been ineffective the use of one of the following methods has to be considered: 1. artificial kidney, 2. peritoneal dialysis, 3. intestinal dialysis, 4. replacement transfusion. Treatment with an artificial kidney is the most widely applied therapy for kidney failure. Substantial improvements have been made in artificial kidney technology during the past decades, such as with regard to membrane technology, dialysate composition, and medication to address side effects.